In situ fabrication of 1D CdS nanorod/2D Ti3C2 MXene nanosheet Schottky heterojunction toward enhanced photocatalytic hydrogen evolution - Xiao, Rong; Zhao, Chengxiao; Zou, Zhaoyong; Chen, Zupeng; Tian, Lin; Xu, Haotian; Tang, Hua; Liu, Qinqin; Lin, Zixia; Yang, Xiaofei (Applied catalysis. B, Environmental, 2020)
[Display omitted] •1D CdS/2D Ti3C2 MXene Schottky heterojunction was successfully fabricated.•In situ constructed Schottky photocatalyst exhibits enhanced HER performance.•Ultrathin 2D MXene enhances light absorption and accelerates charge transport.•The specific Schottky interface is responsible for the improved HER activity. Benefiting from excellent metallic conductivity, full-spectrum solar energy absorption and rich active sites on the surface, atomically thin two-dimensional transition metal carbide (2D MXene) shows great promise in improving solar-to-hydrogen efficiency and has drawn intense interest in the field of photocatalysis. However, controllable construction of ultrathin 2D MXene-based heterojunction photocatalysts still remains a significant challenge. Herein, one-dimensional (1D) CdS nanorod/2D MXene nanosheet heterojunctions with well-defined nanostructures and strong interfacial coupling are fabricated by in situ assembling solvothermally-generated CdS nanorods on ultrathin Ti3C2 MXene nanosheets. Due to their specific interface characteristics, 1D/2D Schottky heterojunction is capable of providing accelerated charge separation and a lower Schottky barrier for solar-driven hydrogen evolution from water splitting. As expected, the Schottky-based photocatalyst is 7-fold more active in the illuminated hydrogen evolution reaction (HER) than pristine CdS nanorods, implying the synergistic effects between n-type semiconductor CdS and highly conductive 2D Ti3C2 MXene nanosheets.